EFFECT OF SERVICE ON CUSTOMER'S INTEREST SAVING IN THE KALBAR SYARIAH BANK, SINGKAWANG BRANCH - Gustina Gustina; Ressy Ressy (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This study aims to determine the effect of services provided by Bank Kalbar Syariah, Singkawang Branch on customers' interest in saving at Islamic Banks. This research uses an associative quantitative approach. The number of research samples was 99 people and the sampling technique used was incidental sampling technique. Primary data obtained directly from the field, namely distributing questionnaires to customers of Bank Kalbar Syariah, Singkawang Branch, totaling 99 respondents. This study uses three data collection techniques, namely: observation, questionnaires and documentation. Validity test uses the product moment formula and the research instrument reliability test uses Alpha Cronbach analysis. While the hypothesis test uses multiple linear regression. The results showed that there was a significant effect of service on customers' interest in saving at Bank Kalbar Syariah, Singkawang Branch. The results of this study were carried out using the assistance of the IBM SPSS Statistics 23 application, as evidenced by the t test results, namely t count (4.119)> t table (0.198) and significance (0.000) <significance (0.05), then the result Ha is accepted.